The osteology and provenance of a portion of the Parkinson collection, Gazelle Peninsula, New Britain, c. 1897. (24th October 2021) - Huffer, Damien
Abstract: This article presents the results of combined osteological and archival research into the demographics, preservation condition, taphonomy, pathology, cultural modification, and collecting history of that specific portion of the Parkinson collection of human crania from New Britain, collected c. 1897, currently housed in the Etnografiska Museet (Ethnography Museum), Stockholm, Sweden. This assemblage of crania ( n = 45) was acquired by Richard Heinrich Robert Parkinson (1844–1909), a Danish explorer and anthropologist initially in the employ of the Hamburg based J. C Goddefroy & Sohn in Samoa trading firm. In 1897, after independently settling on the Gazelle Peninsula of New Britain with his family and beginning to make collecting trips to local communities and those on neighboring islands, this collection of crania eventually came to reside at its present location. This article provides the first in‐depth analysis of the osteology of this collection contextualized within what is known and knowable about its ownership history and movement between collection and arrival in Stockholm. This includes translation of previously untranslateded correspondence from the original German that provide heretofore undisclosed information about Parkinson's collecting activities. Osteological analysis includes age and sex estimation, taphonomic modification as an indicator of initial depositional environment, discussion of select examples of pathology and trauma, and the comparative analysis of decorative motifs (where present). Results indicate a primarily young adult male assemblage, but with all major age classes and both sexes present. Incidents of trauma and pathology are low, but some unique examples are highlighted. The results of the taphonomic analysis reveal new insights into most probable means of primary and secondary deposition before collection and export to Europe. Overall, the work presented here furthers the argument that research into colonial‐era collecting and trading of human remains is most effective when osteological and archival research is conducted together whenever possible.